When external design and marketing collaborate to develop new products: a typology of patterns - Hemonnet-Goujot, Aurélie (2020)
With the rise of open innovation, external design is increasingly called upon, especially by marketing. However, the research on collaboration between external design and marketing in the new product development (NPD) process is still in progress. While the literature suggests that resorting to external design is a means to increase product innovativeness, not all products developed in such a way are innovative. Furthermore, the sources of design expertise are diverse and the strategies that firms use to manage them remain unclear. Thus, this paper aims to identify and analyze the various collaboration patterns between external design and marketing in the NPD process and especially how such patterns affect new product innovativeness. Building on seven case studies, this research proposes a typology of three collaboration patterns between external design and marketing in the NPD process. The first category develops a pattern of collaboration with a strong marketing lead that relies on customer-based designers. The second depicts collaboration with a strong design lead that relies on process-based designers. In the third categorization, a co-branding pattern through collaboration with star-based designers is developed. Theoretical and managerial implications are presented along with the challenges in the complexity of finding the right balance between product innovativeness and brand consistency.